THE 3 MOST COMMON MISTAKES IN IELTS/CEFR PREPARATION: (NOT ADAPTING TO THE EXAM FORMAT, POOR TIME MANAGEMENT, AND INSUFFICIENT - Ravshanova Marjona Jumaniyoz qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article analyzes the three most widespread mistakes that hinder candidates preparing for the IELTS and CEFR exams from achieving high scores. The main goal is to demonstrate that strategic preparation is equally as important as language proficiency itself.The key mistakes examined are:Not Adapting to the Exam Format: Candidates’ lack of understanding regarding the specific question types and scoring criteria in each section.Poor Time Management: The lack of skills necessary to efficiently complete the test within the strict time limits.Insufficient Practice: Neglecting regular and focused practice, especially in the active skills (Writing and Speaking).The article offers practical solutions and strategies to overcome each mistake, emphasizing the necessity of a strategic approach to the preparation process. Adherence to these recommendations will help candidates maximize the demonstration of their knowledge under exam conditions.